2014
DOI: 10.14260/jemds/2014/3668
|View full text |Cite
|
Sign up to set email alerts
|

A Bacteriological Study Among Patients Below Five Years of Age Suffering From Diarrhoea and Gastroenteritis With Special Reference to the Responsible Serotypes of Escherichia Coli at a Tertiary Healthcare Hospital in Eastern Bihar

Abstract: Diarrhoea is defined as passage of loose, liquid or watery stools. In the developing countries, diarrhoea remains a wet season disease with bacteria playing a greater role. The agents responsible for infantile diarrhoea may be bacteria, viruses, parasites, malnutrition and drugs. Infectious agents that cause diarrhoeal disease are usually spread by the fecal-oral route. Escherichia coli (E. coli) is a gram-negative bacillus that may be found in the normal intestinal flora of humans and animals, but can also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This is the first report of molecular epidemiology of DEC pathotypes and occurrence of ESBL-producing strains among diarrheal preschool children from low socioeconomic communities of Patna, Bihar (India). A report from Katihar/Kosi region of Bihar by Muni et al 74 showed that among different types of DEC, the maximum number of strains was EPEC (49.1%), followed by DAEC (34.5%), EAEC (10.9%), and ETEC (5.5%). In another study from India, Singh et al 75 reported DEC in 88.33% of isolates, EPEC (72.5%) being the predominant pathotype followed by EAEC (63.33%), ETEC (45.83%), and EHEC (9.16%).…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report of molecular epidemiology of DEC pathotypes and occurrence of ESBL-producing strains among diarrheal preschool children from low socioeconomic communities of Patna, Bihar (India). A report from Katihar/Kosi region of Bihar by Muni et al 74 showed that among different types of DEC, the maximum number of strains was EPEC (49.1%), followed by DAEC (34.5%), EAEC (10.9%), and ETEC (5.5%). In another study from India, Singh et al 75 reported DEC in 88.33% of isolates, EPEC (72.5%) being the predominant pathotype followed by EAEC (63.33%), ETEC (45.83%), and EHEC (9.16%).…”
Section: Discussionmentioning
confidence: 99%